Structure and activity of bioactive peptides produced from soybean proteins by enzymatic hydrolysis. (October 2022) - Wen, Lingrong; Bi, Huimin; Zhou, Xuesong; Zhu, Hong; Jiang, Yueming; Ramadan, Nehal S.; Zheng, Rongbo; Wang, Yu; Yang, Bao
Highlights: Soybean peptides were produced by Alcalase®-neutrase stepwise hydrolysis. Eighty five soybean peptides were identified by UHPLC-MS/MS. NF-κB and JNK pathways were regulated by soybean peptides. Soybean peptides induced the production and genes expression of NO, IL-6 and TNF-α. Abstract: Peptides are good food stabilizers and thickeners. They also present good bioactivities. The structure characteristics of peptides are related to the health benefits. In this study, immunoregulatory peptides were produced by Alcalase® and neutrase hydrolysis of soybean proteins. UHPLC-MS/MS was applied for structure identification. The immumoregulatory activities and mechanisms were investigated. Eighty five peptides were identified from the hydrolysates and 84 peptides might be immunoregulatory peptides. Most of them were novel immunoregulatory peptides. These peptides had good immunoregulatory activities, including increasing the pinocytotic capacity, and inducing the production and genes expression of NO, IL-6 and TNF-α in a dose-dependent manner. Specific inhibitors of NF-κB and JNK could significantly suppress NO production stimulated by soybean peptides, implying that NF-κB and JNK pathways were involved in their immunoregulatory mechanisms. Our results suggested that the soybean peptides prepared in this study were promising immunomodulatory neutraceuticals.